Writing Scholarly Papers: A Window from my Experiences - Dickson Adom (ASEAN Multidisciplinary Research Journal, 2021)
This article discusses time-tested strategies for scholarly writing to assist early career researchers. It highlights the experiences of the author on how to become a successful scholarly writer. It discusses the need to follow research integrity and excellence required in scholarly writing as well as the essence of conciseness and clarity in research communication as key ingredients of scholarly writing. It examines the significant roles played by professional training, mentorship, and volunteering in giving researchers the skills and knowledge required for scholarly writing. The article assures that though scholarly writing may be seen as an intimidating activity wrought with a lot of challenges, it is an achievable goal for not only seasoned researchers but also early career researchers who are determined to share their novel research outputs with the global academic community.